Towards more affordable medicine: A proposal to waive certain obligations from the Agreement on TRIPS - Biswajit Dhar; K. M. Gopakumar (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2020)
Access to medicines at prices patients can afford has been a recurrent concern for the global community ever since the Agreement on Trade Related Aspects of Intellectual Property (TRIPS) was adopted in 1995 as one of the agreements under the World Trade Organization (WTO). In 2001, WTO Members emphasised that the "TRIPS Agreement does not and should not prevent Members from taking measures to protect public health ... and that the Agreement can and should be interpreted and implemented in a manner supportive of WTO Members' right to protect public health and, in particular, to promote access to medicines for all" (World Trade Organization 2001: paragraph 4). Subsequently, the adoption of the Doha Declaration provided clarity with regard to the flexibilities in the TRIPS Agreement and many developing countries used these flexibilities to facilitate access to medicines when in need (especially in the HIV/AIDS context). Such need might have again occurred with the COVID-19 pandemic. Using the recently submitted proposal by India and South Africa, discussed by the TRIPS Council in the WTO in October 2020, this working paper discusses some possible ways forward in dealing with some specific obligations under the Agreement on TRIPS with an objective of enhancing world's chances for prevention, containment, and treatment of COVID-19.
Keywords: F14; I11; O33; 330; waiver; pharmaceuticals; TRIPS; India; South Africa; WTO; WIPO; medicine; vaccine; COVID-19